STUDI KESESUAIAN AREAL UNTUK BUDIDAYA LAUT DI PERAIRAN PULAU KARAMPUANG SULAWESI BARAT - SUDIRMAN ADIBRATA; MARZUKI UKKAS; KUKUH HARIADI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
The research takes 6 stations based on point of compass in the water of Karampuang Island – West Sulawesi Province. The goal of this research is to know feasibility area sight from oceanography physics and chemics for marine culture of seaweed with rope in upper water, floating nets of kerapu fish, sea cucumber and abalone marine culture. Analysis method of feasibility area with the quality for a piece of biophysics parameter is measured not only for supporting factor but also breaking factor for marine culture. The research of feasibility by calculating the total score from all parameters measured in situ with feasibility criteria that the feasibility area is very, enough, and not properly. The seaweed marine culure with with rope in upper water is very proper to develop into the six stations of research, kerapu fish at the station 1,2,3,5 and 6. Sea cucumber at the station 1,2,3, and 4. Pearl Oyster is very proper at the station 1 and 2 and others shows that they are only proper enough with marine culture because of the marine limited factor is bigger than supporting factors